1969
DOI: 10.1111/j.1365-2621.1969.tb01531.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characteristics of processed whole egg

Abstract: Flow curves determined with a rotational Viscometer have shown that unfrozen raw and pasteurized liquid whole egg are Newtonian fluids and that thawed frozen whole egg is pseudo-plastic. For the latter a useful value for comparative purposes may be obtained by calculating the apparent viscosity at a selected low rate of shear. Some preliminary results illustrate the very large difference in viscosity between unfrozen egg and thawed frozen egg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Large differences in the viscosity of fresh and frozen LWE have been reported (Cornford et al, 1969;Palmer et al, 1969;Harrison and Cunningham, 1986). Frozen storage at −20°C for 2 months doubled the viscosity of LWE compared to controls (Torten and Eisenberg 1982).…”
Section: Rheological Parametersmentioning
confidence: 97%
See 1 more Smart Citation
“…Large differences in the viscosity of fresh and frozen LWE have been reported (Cornford et al, 1969;Palmer et al, 1969;Harrison and Cunningham, 1986). Frozen storage at −20°C for 2 months doubled the viscosity of LWE compared to controls (Torten and Eisenberg 1982).…”
Section: Rheological Parametersmentioning
confidence: 97%
“…Frozen storage at −20°C for 2 months doubled the viscosity of LWE compared to controls (Torten and Eisenberg 1982). Cornford et al (1969) and Torten and Eisenberg (1982) reported that thawed frozen whole egg was pseudoplastic. Processors have reported occasional variability in the functionality of frozen LWE used in commercially prepared baked goods.…”
Section: Rheological Parametersmentioning
confidence: 99%
“…The rheological characteristics of egg liquids have been studied by several authors who reported Newtonian, as well as timedependent non-Newtonian, flow behavior of the egg (Cornford et al, 1969Ibarz et al, 1999Punidadas and Mckellar, 1999;Alamprese et al, 2005Severa et al, 2005Telis-Romero et al, 2006Dauphas et al, 2007Atilgan and Unluturk, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…This knowledge is essential for the product development, quality control, sensory evaluation and design and evaluation of the process equipment (Velez-Ruiz, 2002). Several researchers (Kaufman et al 1968;Cornford et al, 1969;Scalzo et al 1970;Tung et al, 1971;Hamid-Samimi et al 1984;Ibarz and Sintes, 1989;Lee et al, 1999;Punidadas and McKellar, 1999;Telis-Romero et al, 2006;Toyosaki, 2010) studied the rheological characteristics of egg and reported Newtonian as well as time-dependent Non-Newtonian flow behaviour of egg. These works are summarized in (Atilgan and Unluturk, 2008).…”
Section: Introductionmentioning
confidence: 97%